(untitled) (Bangladesh Journal of Medical Science, 2022)
Introduction: Angiotensin converting enzyme 2 (ACE2) is expressed in several cell types in the body including the gastrointestinal (GI) epithelium. Objective:To provide an overview of the normal distribution of ACE2 in the GI tract, altered ACE2 expression notably in coronavirus infection and its consequences. Materials and Methods: Pubmed and google scholar were searched using the key words ACE2 paired with GI tract, intestinal permeabilty, gut microbiota, inflammatory bowel disease. Results and Discussion: ACE2 is highly expressed in the ileum and colon in human being as well as in rodents. In this current situation of COVID-19 pandemic, downregulation of ACE2 has been reported due to internalization of the ACE2-virus complex within the cells. Although researches are still in infancy in this topic, altered luminal microbiota, increased intestinal permeability, higher level of inflammatory markers and deficient nutrient transport has been reported due to altered ACE2 expression. Conclusion:Altered expression of ACE2 has the possibility to hamper normal physiological function of the GI tract and might affect GI disease progression and prognosis. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 808-812